Implementasi Program Ternak Lele dan Tanaman Banyak Jenis (Teletabis) di Sekolah Dasar Negeri 2 Guno Kabupaten Wonogiri - Nugroho, Rizal Aldi; Prabawati, Indah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Innovation in various fields, including education, is key to improving regional performance and community welfare. Wonogiri Regency demonstrates a strong commitment to encouraging innovation within its area. The Catfish Farming and Multi-Crop Planting Program (TELETABIS) at SDN 2 Guno is a practical, education-based innovation aimed at enhancing students' skills in agriculture and fisheries through an aquaponic system. This study aims to analyze the implementation of the TELETABIS program using Smith's policy implementation model. The research method employed is a qualitative approach with data collection techniques comprising observation, interviews, and documentation. The results show that the TELETABIS policy has been well-designed. Students, as the target group, showed high enthusiasm in participating in the program, especially during the harvest period, although their level of involvement varied. The implementing organization, consisting of the principal, teachers and staff, has run the program systematically, although it still faces obstacles, namely the lack of monitoring, evaluation and attention to the sustainability of the program. Environmental factors also posed challenges, such as limited support from the village government, scarce economic resources, and low community involvement in sustaining the program. In conclusion, the TELETABIS program provides tangible benefits for students and the school environment but still requires improvements in the monitoring system, regular evaluation, and collaboration with external parties to ensure more optimal and sustainable implementation. Therefore, this study recommends improving the monitoring system and increasing attention to the programs sustainability, optimizing support from the school committee and parents, as well as empowering aquaponics for the surrounding community so that the benefits of this valuable program can be more widely experienced.